(untitled) (The Review of Diabetic Studies, 2024)
The benefits of effective leadership in health systems cannot be overstated. There was a serious gap in knowledge regarding which particular styles of leadership have the biggest impact on organizational performance in the Saudi Arabian government health sector, where the situation is rapidly changing. This research aimed to establish the correlations between transformational and transactional leadership styles, passive-avoidance, and key performance indicators, which is a significant knowledge gap in relation to specific leadership development. A correlational, cross-sectional design has been used where 185 senior and middle health managers in the public hospitals and primary care centers were surveyed using the Multifactor Leadership Questionnaire and a validated Organizational Performance Scale. This showed that transformational leadership was the best positive predictor of organizational performance ( = 0.55, p < 0.001), contingent reward the next best positive predictor ( = 0.18, p = 0.003), and passive leadership the significant negative predictor ( = -0.23, p < 0.001). The regression model registered 62 percent of the explanation of the variance in performance (Adjusted R 2 = 0.62). In addition, scores of transformational leaderships were very high among senior managers compared to the middle managers (p < 0.001). It was established that the development of transformational leadership skills, especially at the middle management level, is a strategic requirement for the effectiveness and sustainability of the Saudi Arabian public health system. Such results, in turn, form the evidence-based basis of human resource policies and leadership capacity-building programs in accordance with the transformation objectives in the health sector of the country.